SDM BPP Dalam Pelaksanaan Jombang One Stop Service (JOSS): (Ditinjau dari Impelementasi dan Efektifitas Organisasi) - Aslichah; Khoiruddin; Wahyu Aris Setyawan (Journal of Public Power, 2022)
The purpose of this research is to describe and interpret the implementation of Jombang One Stop Service (JOSS) and its effectiveness in Jombang Regency from the procedural aspect, human resource aspect, time-cost aspect, and infrastructure aspect. The writing of this study used a qualitative descriptive method, data collection was carried out by observation and interviews with the location of BPP Jombang Regency which is located at Jln Merdeka No. 151 Jombang. The data collection methods used are: Library Research, and Field Research. The technique of determining the information used in this research is purposive sampling. The data analysis technique in accordance with this research is descriptive qualitative analysis with Data Reduction, Data Display and Conclusion Verification. From the results of observations and surveys, it can be concluded that the aspects of the procedure can be accepted by the community well. The dissemination of regulations and licensing procedures that have been carried out is good and can be understood by the public; on the aspect of human resources generally shows good performance. The performance of human resources in this discussion is that in providing services, officers have done it with discipline, responsibility; officers have the ability to provide services, have been fair and courteous in serving the community; on the aspect of cost and time, it shows that the certainty or accuracy of implementation of the service time schedule that has been set in the Jombang One Stop Service (JOSS) BPP Jombang Regency is still not satisfying the community or is still low; in the aspect of infrastructure is quite good and improvements in infrastructure continue to be made. Meanwhile, the effectiveness of human resource services related to the certainty or accuracy of implementation of the service time schedule is still not optimal.